Чотиримірний простір і вектор струму зсуву - Придубков, П.Я.; Хоменко, І.В. (Електротехніка і електромеханіка, 2011)
Application of vector and scalar potentials for computation of the principal electromagnetic field vectors is considered. Formation of the given field 4-D tensor components with 4-D potential derivatives is shown, expression for bias current in terms of the potentials is derived.